INTERLEUKIN-1 FAMILY: FROM GENES TO HUMAN DISEASE - Laurincová, Beáta (Biomedical papers, 2000)
Interleukin-1 (IL-1) is one of the most potent proinflammatory cytokines involved both in physiologicalimmune responses and in the development of various immunopathological disorders. The members of IL-1 familyform a complex system with tight regulatory mechanisms and clarifying their role in disease remains in the centre ofresearch interests. This review article except of summarising recent findings about IL-1 family members focuses onassociations of IL-1 gene complex polymorphisms with human diseases.
Keywords: Interleukin-1 / Interleukin-1 receptor antagonist / Gene polymorphism